2009
DOI: 10.3109/09638280903362712
|View full text |Cite
|
Sign up to set email alerts
|

Client and therapist views on exercise programmes for early-mid stage Parkinson's disease and Huntington's disease

Abstract: Therapists should work in collaboration with clients to evaluate their individual considerations, identify barriers to exercise and design a client-specific programme that is acceptable and feasible for the client.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 48 publications
(56 reference statements)
6
59
0
8
Order By: Relevance
“…62 Other studies of people with PD have suggested that a patient-centered approach, in which therapists work in partnership with people to facilitate a better understanding of the goals and outcomes expected from exercise, also may help to increase self-efficacy. 31,63 The results of the present study may have been influenced by differences in the characteristics of the exercise and nonexercise groups. For example, the nonexercise group had a longer duration of PD; however, disease severity, as measured by H&Y stage, did not differ between the exercise group and the nonexercise group.…”
Section: Barriers To Exercise In People With Parkinson Diseasementioning
confidence: 72%
See 1 more Smart Citation
“…62 Other studies of people with PD have suggested that a patient-centered approach, in which therapists work in partnership with people to facilitate a better understanding of the goals and outcomes expected from exercise, also may help to increase self-efficacy. 31,63 The results of the present study may have been influenced by differences in the characteristics of the exercise and nonexercise groups. For example, the nonexercise group had a longer duration of PD; however, disease severity, as measured by H&Y stage, did not differ between the exercise group and the nonexercise group.…”
Section: Barriers To Exercise In People With Parkinson Diseasementioning
confidence: 72%
“…30 A lack of a patientcentered approach to prescribing exercise may further limit motivation and outcome expectations. 31 The purpose of the present study was to identify barriers to exercise in people who have PD and dwell in the community. All evaluators were provided with a standard operating procedures manual and an instructional video that described the protocol for administering and scoring each instrument for 2 participants with PD.…”
Section: Barriers To Exercise In People With Parkinson Diseasementioning
confidence: 99%
“…Including an unsupervised home programme as part of an intervention reduces the burden on resource limited physiotherapy services, promotes autonomy and enables patients to increase their physical activity levels. A range of opportunities to participate in exercise interventions, such as groups or individually delivered sessions, should be available in practice in order to meet the needs of differing patient circumstances and motivations 27 28…”
Section: Discussionmentioning
confidence: 99%
“…These findings are reflected in the recent review by York and Wiseman (2012) and by the results in this study. The desirability of physical exercise and leisure for HD clients is mentioned in studies by Quinn et al (2010) and McCabe, Roberts, and Firth (2008) but gardening is not mentioned as a possible activity in either paper.…”
Section: Discussionmentioning
confidence: 94%